Ten Monsters in the Bed - Cotton Katie (Gosford; Scholastic, 2014)
Annotation. A monstrous take on 'Ten Green Bottles' and Ten in the Bed with farty, burpy, slurpy sounds! Ten monsters are very squished on a bunk bed. On each spread, a monster gets pushed out onto the floor, making a disgusting noise. Eventually, all the monsters end up on the floor ... and realise theyre more squished than ever!
Keywords: Stories in rhyme